2022
DOI: 10.3390/pr10030520
|View full text |Cite
|
Sign up to set email alerts
|

Application Research of Soft Computing Based on Machine Learning Production Scheduling

Abstract: An efficient and flexible production system can contribute to production solutions. These advantages of flexibility and efficiency are a benefit for small series productions or for individual articles. The aim of this research was to produce a genetic production system schedule similar to the sustainable production scheduling problem of a discrete product assembly plant, with more heterogeneous production lines, and controlled by one-time orders. First, we present a detailed mathematical model of the system un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Thus, machine learning streamlines structured data such as imaging, medical history, or histopathologic results to attempt to cluster a patient’s traits and act upon it, while natural language processing methods extract information from unstructured data to supply addition to available data settings [ 28 , 45 ]. Therefore, the potential for artificial intelligence in healthcare is predominantly seen in leveraging performance and efficiency, enhancing clinical decision quality, actively managing specific health populations, and empowering patients and providers [ 6 , 8 , 28 , 43 , 44 , 46 , 47 ]. As such, an artificial intelligence system is able to evaluate masses of data through algorithmic analysis to encompass automation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, machine learning streamlines structured data such as imaging, medical history, or histopathologic results to attempt to cluster a patient’s traits and act upon it, while natural language processing methods extract information from unstructured data to supply addition to available data settings [ 28 , 45 ]. Therefore, the potential for artificial intelligence in healthcare is predominantly seen in leveraging performance and efficiency, enhancing clinical decision quality, actively managing specific health populations, and empowering patients and providers [ 6 , 8 , 28 , 43 , 44 , 46 , 47 ]. As such, an artificial intelligence system is able to evaluate masses of data through algorithmic analysis to encompass automation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our investigations have shown that this solution does not provide sufficient convergence and that the motions in our problem are different from it, but several elements of the basic model can be incorporated into our model. A similar and similarly unsuccessful attempt based on swarm intelligence is presented in [3], where an evolutionary algorithm was also chosen as the suitable approach. Another approach that can be used concerns automatic parking systems.…”
Section: Path Planningmentioning
confidence: 99%
“…Therefore, when the production equipment is in operation, it is impossible to collect and summarize the product information in real time, nor is it possible to carry out early warning and historical tracing based on the collected data information. [4][5][6] This results in the low output and slow progress of traditional production line. Besides, it is difficult to detect the failure in the operation of the equipment promptly, which causes a high rate of defective products.…”
Section: Introductionmentioning
confidence: 99%